Fibrous supercapacitor
By using composite electrode materials, special electrolytes and advanced process methods in fibrous supercapacitors, the challenges of existing fibrous supercapacitors in electrode activity, ion migration speed and structural stability are solved, and significantly improved energy density, power density and cyclic stability are achieved to meet the needs of complex environments.
Patent Information
- Application Number
- CN202510124109.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-25
AI Technical Summary
Existing fibrous supercapacitors have multiple challenges in electrode materials, electrolytes and preparation processes, including insufficient electrode activity, slow ion migration speed, unstable structural structure and degradation in low temperature and complex stress environments, resulting in hindering their commercialization and practicalization processes.
The composite carbon nanotube fiber electrode and metal oxide-polymer composite electrode are used, combined with gel electrolyte and ionic liquid electrolyte, and the coaxial fiber structure and braided device structure are used to prepare through electrospinning and in-situ polymerization process, and real-time monitoring and adjustment are further carried out through an intelligent monitoring system and microstructure detection device.
It significantly improves the energy density, power density and cycle stability of fibrous supercapacitors, extends service life, and improves the efficiency of the preparation process and product consistency, can maintain high capacitance performance in low temperature environments, and adapt to complex stress environments.
Abstract
Description
Technical Field
[0001] The invention relates to the field of information management systems, and in particular to a fiber-shaped supercapacitor. Background Art
[0002] With the rapid development of wearable technology and the Internet of Things industry, the market demand for flexible energy storage devices is increasing day by day. Traditional block supercapacitors are limited by their shape and flexibility, making it difficult to embed them into thin, bendable devices such as smart clothing and micro sensors. Fiber-shaped supercapacitors have emerged as the key to breaking the deadlock. However, they are currently in deep trouble.
[0003] From the perspective of electrode materials, most existing fiber electrodes have limited specific capacitance. Pure carbon-based materials, such as common carbon nanotube fibers, have acceptable conductivity, but their pseudocapacitance contribution is insufficient and energy storage sites are scarce; when metal oxides or conductive polymers are used alone, they face the problems of poor conductivity and poor mechanical properties, resulting in low overall electrochemical activity of the electrode and inability to store large amounts of charge. In terms of electrolytes, conventional gel electrolytes have slow ion migration rates, just like traffic jams, making the charging and discharging process time-consuming; ionic liquid electrolytes have the shortcoming of a narrow electrochemical window, and the operating voltage is limited, which directly lowers the energy density.
[0004] In terms of preparation technology, when preparing fiber electrodes by electrospinning, the parameters are often not precisely controlled, resulting in poor uniformity and lack of continuity of the produced fibers, resulting in low yields and difficulty in meeting the stringent requirements of large-scale production. The device structure also lacks ingenuity, and the simple structure cannot take into account both rapid ion diffusion and efficient charge storage, limiting the overall performance. Moreover, there is a lack of consideration for actual usage scenarios, and the capacitance drops sharply in low-temperature environments. After a few uses, the performance drops off a cliff, not to mention dealing with emergencies such as microcracks in the electrodes under complex stress environments. All these drawbacks seriously restrict the commercialization and practical application of fiber-shaped supercapacitors, and innovative means are urgently needed to resolve the problem. Summary of the invention
[0005] The present invention provides a fiber-shaped supercapacitor, comprising:
[0006] An electrode material, wherein the electrode material is a composite carbon nanotube fiber electrode, which is composited with multi-walled carbon nanotubes (MWCNTs) and nitrogen-doped graphene quantum dots (NGQDs), wherein the NGQDs account for 10%-20%, and contain cobalt acetate (Co(Ac)2), a cobalt-containing organic compound, which accounts for 0.1%-0.3% of the total mass; or a metal oxide-polymer composite electrode, wherein manganese dioxide (MnO2) nanosheets are uniformly dispersed in a polypyrrole (PPy) fiber matrix by in-situ polymerization, and the MnO2 content is controlled at 30%-40%;
[0007] The electrolyte is a gel electrolyte, with polyvinyl alcohol (PVA) as the skeleton, and a mixed lithium salt of lithium perchlorate (LiClO4) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) is incorporated, the molar ratio of the two is 1:2-1:3, the total concentration of the lithium salt is maintained at 3-5 mol / L, and contains 0.5%-1% of the total mass of the electrolyte, the fluorine-containing organic compound ammonium perfluorooctanoate (APFO); or an ionic liquid electrolyte, composed of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) salt (BMIMNTf2) The mixed ionic liquid system, the volume ratio is 2:1-3:1, and contains 0.01%-0.03% of the total mass of the vanadium-containing organic compound acetylacetonate vanadium (V(Acac)3);
[0008] The device structure adopts a coaxial fiber structure, with MWCNTs-NGQDs composite fiber as the inner core, a layer of MnO2-PPy composite fiber coated on the outside, and a gel electrolyte layer wrapped on the outermost layer with a thickness of about 50-100μm; or a woven device structure, in which multiple fibrous supercapacitors are woven into a two-dimensional or three-dimensional network structure.
[0009] The fibrous supercapacitor according to claim 1 is characterized in that the preparation method of the composite carbon nanotube fiber electrode is: using an electrospinning method, accurately controlling the spinning voltage at 15-25 kV, the receiving distance at 10-20 cm, the flow rate at 0.5-1 mL / h, and adding a surfactant sodium dodecyl sulfate (SDS) accounting for 0.5%-1% of the mass of the precursor solution.
[0010] Furthermore, the preparation method of the gel electrolyte comprises: mixing polyvinyl alcohol, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide and ammonium perfluorooctanoate in proportion, and performing stirring, heating and degassing treatment to uniformly disperse the components.
[0011] Furthermore, the preparation method of the ionic liquid electrolyte includes: mixing 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt according to a set volume ratio, adding vanadium-containing organic compound vanadium acetylacetonate, and stirring evenly under the protection of inert gas.
[0012] Furthermore, the assembly process of the fibrous supercapacitor with the coaxial fiber structure is completed on a continuous roll-to-roll production process line, and the parameters of each link are monitored in real time throughout the process from electrode fiber preparation, electrolyte coating to device packaging.
[0013] Furthermore, it also includes a performance monitoring and control system, which is an in-situ cyclic voltammetry (CV), constant current charge and discharge (GCD) and electrochemical impedance spectroscopy (EIS) joint testing system for real-time tracking of the specific capacitance, internal resistance and coulombic efficiency of the fibrous supercapacitor during the preparation process and aging stage. When the specific capacitance drops by more than 3% or the internal resistance increases by more than 5%, the subsequent process parameters are automatically adjusted.
[0014] Furthermore, the system is also equipped with a microstructure detection device, which is an online monitoring system combining a scanning electron microscope (SEM) and a transmission electron microscope (TEM). The SEM is used to capture the surface morphology and pore conditions of the material, and the TEM is used to analyze the internal structure and nanostructure characteristics of the grains. Once an abnormality is found, the preparation process can be adjusted immediately.
[0015] Furthermore, it can be applied to the energy supply of smart clothing. The fiber-shaped supercapacitors can be woven into the clothing fabric and cooperated with other energy harvesting devices to collect human movement energy and ambient light energy to continuously power the built-in components of the clothing.
[0016] Furthermore, it is applied to self-powering of IoT sensors and integrated into IoT sensor nodes, utilizing high power density and fast charging and discharging characteristics to capture and store environmental micro-vibrations and temperature difference energy.
[0017] Furthermore, when synthesizing the electrolyte, an organic additive containing ethylene glycol is added at a weight percentage of 5% to 10% of the total raw material weight to ensure that the capacitance decay amplitude is less than 15% in a low temperature environment of -20°C;
[0018] The electrode material incorporates 0.5%-1% of disulfide bond-containing organic small molecules by mass. When microcracks appear inside the electrode, the disulfide bonds break and reconnect under heat or light stimulation to repair the microcracks. Based on the microelectromechanical system (MEMS) process, customized production of micro-fibrous supercapacitors can be achieved to meet the stringent demands of implantable medical devices, micro-sensors, etc. for tiny energy storage devices.
[0019] Beneficial effects:
[0020] The performance of the fiber-shaped supercapacitor is improved in all aspects under the optimization of the present invention. In terms of energy density, the composite electrode material and the special electrolyte work together to increase it by 30%-50% compared with traditional products, which means that more electricity can be stored in the same volume, bringing hope to wearable devices that are anxious about battery life. The power density is increased by 20%-40%, and fast charging and discharging becomes a reality. Devices such as smart bracelets that require frequent short-term recharges can be revitalized in the blink of an eye. Cycle stability is a highlight. After 10,000 charge and discharge cycles, the capacitance retention rate is >90%, which greatly extends the service life, reduces the frequency of equipment updates, and cuts costs.
[0021] In terms of preparation technology, the upgraded electrospinning and continuous roll-to-roll process have increased production efficiency by 40%-60%, and the yield rate has also increased by 30%-50%. Product consistency is guaranteed, paving the way for large-scale industrial production. The intelligent monitoring system tracks performance in real time, with a deviation of less than 3%, and the quality is as stable as Mount Tai. With the incorporation of ethylene glycol additives, the capacitance decay amplitude is less than 15% in low temperature environments, and the equipment can operate normally in cold northern regions or high-altitude low-temperature scenes. Small molecules containing disulfide bonds give the electrode self-healing ability, microcracks heal quietly, and the device life is further extended. Miniaturization customization uses MEMS technology to meet the needs of niche but key fields such as implantable medical devices and microsensors, broaden the application boundaries, and make fiber-shaped supercapacitors truly a powerful energy storage tool in the era of flexible electronics. DETAILED DESCRIPTION
[0022] Example 1: Preparation and performance testing of composite carbon nanotube fiber electrodes
[0023] Preparation method Raw material preparation: Accurately weigh multi-walled carbon nanotubes (MWCNTs), nitrogen-doped graphene quantum dots (NGQDs) and cobalt acetate (Co(Ac)2), a cobalt-containing organic compound. Ensure that NGQDs account for 15% of the total mass and Co(Ac)2 accounts for 0.2%. Disperse them in N,N-dimethylformamide (DMF) solvent to form a uniform precursor solution, and maintain the total solute concentration at 10-15wt%.
[0024] Electrospinning parameter setting: The precursor solution was loaded into the syringe of the electrospinning device, the spinning voltage was adjusted to 20 kV, the receiving distance was set to 15 cm, and the flow rate was precisely controlled at 0.8 mL / h. At the same time, the surfactant sodium dodecyl sulfate (SDS) was added at 0.8% of the mass of the precursor solution and stirred thoroughly.
[0025] Spinning process: Turn on the electrospinning equipment and spin at an ambient temperature of 25±2°C and a relative humidity of 40-50%. The spinning process lasts for 3-4 hours, and the fibers are evenly deposited on the receiving roller to form continuous composite carbon nanotube fibers.
[0026] Post-treatment: The collected fibers were placed in a vacuum oven and dried at 80°C for 12 hours to remove residual solvent and enhance the mechanical strength and stability of the fibers.
[0027] Efficiency verification
[0028] Improved specific capacitance: A three-electrode system was used, with the prepared fiber as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel electrode (SCE) as the reference electrode, and cyclic voltammetry was performed in a 6M KOH electrolyte. The test results showed that compared with the pure MWCNTs fiber electrode without the addition of NGQDs and Co(Ac)2, the specific capacitance increased from 50F / g to 120F / g, an increase of up to 140%. This is due to the pseudocapacitance contribution of NGQDs and the catalytic generation of Co(Ac)2 on active sites.
[0029] Enhanced conductivity: The conductivity of the fiber was measured by the four-probe method, and it was found that the conductivity of the treated fiber reached 1000S / cm, which is about 67% higher than the 600S / cm of the original MWCNTs fiber, accelerating the charge transfer and laying the foundation for high power density.
[0030] Example 2: In-situ polymerization and performance optimization of MnO2-PPy composite electrode
[0031] Preparation method
[0032] Preparation of polymerization solution: First, dissolve pyrrole monomer in deionized water to prepare a 0.5M pyrrole solution. Then, ultrasonically disperse manganese dioxide (MnO2) nanosheets in the pyrrole solution to ensure that the MnO2 content is 35%. Then add an appropriate amount of initiator ammonium persulfate (APS), and the molar ratio of APS to pyrrole is 1:1.2.
[0033] In-situ polymerization: The mixed solution was transferred to a reactor equipped with a stirring and temperature control device, heated to 5°C, and stirred under a nitrogen atmosphere for 3 hours. As the reaction proceeds, pyrrole will polymerize in-situ on the surface of the MnO2 nanosheets to form MnO2-PPy composite fibers.
[0034] Washing and drying: After the reaction is completed, the product is washed with deionized water and ethanol alternately for 3-5 times to remove unreacted monomers and impurities. Subsequently, it is dried in a vacuum oven at 60°C for 24 hours to obtain a dry composite electrode fiber.
[0035] Efficiency verification
[0036] Capacitance stability: Constant current charge and discharge tests were also conducted in a three-electrode system and 6M KOH electrolyte. After 5000 charge and discharge cycles, the capacitance retention rate of the MnO2-PPy composite electrode reached 92%, while the capacitance retention rate of the single PPy electrode was only 70% under the same test conditions. The introduction of MnO2 effectively improved the stability of the electrode structure and suppressed the volume expansion and contraction of PPy during the charge and discharge process.
[0037] Improved energy density: Calculating energy density based on the charge and discharge curve, the energy density of the MnO2-PPy composite electrode can reach 30Wh / kg, which is about 67% higher than the 18Wh / kg of a single PPy electrode, providing a guarantee for high energy density energy storage.
[0038] Example 3: Optimization of gel electrolyte and ion conductivity test
[0039] Preparation method: Mix raw materials: Add polyvinyl alcohol (PVA), lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and fluorine-containing organic compound ammonium perfluorooctanoate (APFO) in sequence in a three-necked flask with heating and stirring functions. The molar ratio of LiClO4 to LiTFSI is 1:2.5, the total concentration of lithium salt is 4 mol / L, and APFO accounts for 0.8% of the total mass of the electrolyte. Add appropriate amount of deionized water to make the PVA concentration 10wt%.
[0040] Heating and stirring: Heat the three-necked flask to 90°C and react for 4-5 hours under continuous stirring until the solution becomes uniform and transparent and forms a gel electrolyte. During this period, stir continuously to prevent local overheating and agglomeration.
[0041] Degassing treatment: The obtained gel electrolyte was transferred to a vacuum degassing box and degassed at a vacuum degree of -0.1 MPa for 30 minutes to remove internal bubbles and ensure the uniformity of the electrolyte.
[0042] Efficiency verification
[0043] Improved ion conductivity: The ion conductivity was measured by AC impedance method, and the ion conductivity of the optimized gel electrolyte reached 15mS / cm, which is nearly 88% higher than the traditional gel electrolyte (8mS / cm) without APFO. This is because the fluorine element in APFO improves the ion migration environment and reduces the ion migration resistance.
[0044] Anti-drying performance: The electrolyte samples were placed in an environment of 60°C and 30% relative humidity for 7 days. The mass loss of the gel electrolyte with added APFO was only 5%, while the mass loss of the control group without APFO was 20%, indicating that APFO significantly enhanced the stability of the gel and prevented the electrolyte from drying up.
[0045] Example 4: Assembly and performance evaluation of coaxial fiber structure supercapacitor
[0046] Assembly method: Preparation of inner core fiber: Select the composite carbon nanotube fiber electrode prepared in Example 1, cut it to a suitable length, clean the surface with ethanol to remove impurities, and dry it in a nitrogen atmosphere for later use.
[0047] Outer fiber coating: The MnO2-PPy composite electrode fiber prepared in Example 2 is evenly coated on the carbon nanotube fiber through a winding process to ensure that the coating is tight and uniform to form a double-layer fiber structure.
[0048] Electrolyte coating: The prepared gel electrolyte is slowly coated on the outer layer of the double-layer fiber by dip coating, and the coating speed is controlled to be 1-2 mm / s, and finally an electrolyte layer with a thickness of about 80 μm is formed to obtain a supercapacitor with a coaxial fiber structure.
[0049] Efficiency verification
[0050] Charge transfer efficiency: Through the electrochemical impedance spectroscopy (EIS) test, the charge transfer resistance (Rct) of the coaxial structure supercapacitor is 10Ω, which is about 67% lower than that of the same electrode combination with ordinary parallel structure (Rct=30Ω), indicating that the coaxial structure greatly shortens the ion diffusion distance and accelerates charge storage and transfer.
[0051] Overall capacitance improvement: Constant current charge and discharge tests were conducted. At a current density of 1A / g, the specific capacitance of the coaxial fiber structure supercapacitor reached 180F / g, which is 50% higher than the same electrode material combination (120F / g) without a coaxial structure. The overall energy storage performance is significantly enhanced.
[0052] Example 5: Fabrication and flexibility testing of braided fiber supercapacitor
[0053] Preparation method
[0054] Fiber preparation: prepare a plurality of composite carbon nanotube fiber electrodes of Example 1 and MnO2-PPy composite electrode fibers of Example 2, cut fibers of equal length, wash with acetone and then dry.
[0055] Weaving process: Using a weaving machine similar to textile weaving, the two fibers are woven into a two-dimensional plane structure in a specific warp and weft interweaving method. The weaving density is set to 10 fibers per square centimeter and the weaving angle is 45°. During the weaving process, moderate tension should be maintained to avoid fiber breakage or uneven winding.
[0056] Electrolyte injection: After weaving is completed, the optimized gel electrolyte is slowly injected into the woven structure by dripping until the electrolyte fully soaks each fiber, completing the production of the woven fiber supercapacitor.
[0057] Efficiency verification and flexibility evaluation: The braided supercapacitor was subjected to repeated bending tests. After bending 1,000 times with a radius of 5 mm, the capacitance retention rate reached 95%, and the internal resistance only increased by 8%. Compared with similar capacitors with rigid structures, it shows excellent flexibility and mechanical stability, and can better adapt to the frequent deformation requirements of wearable devices.
[0058] Area capacitance improvement: Test the unit area capacitance, the area capacitance of the braided structure reaches 200mF / cm 2 , than non-woven discrete fiber combination (120mF / cm 2 ) is increased by about 67%. The synergy between fibers is optimized through weaving to improve the overall energy storage capacity.
Claims
1. A fiber-shaped supercapacitor, characterized in that: include: An electrode material, wherein the electrode material is a composite carbon nanotube fiber electrode, which is composited with multi-walled carbon nanotubes (MWCNTs) and nitrogen-doped graphene quantum dots (NGQDs), wherein the NGQDs account for 10%-20%, and contain cobalt acetate (Co(Ac)2), a cobalt-containing organic compound, which accounts for 0.1%-0.3% of the total mass; or a metal oxide-polymer composite electrode, wherein manganese dioxide (MnO2) nanosheets are uniformly dispersed in a polypyrrole (PPy) fiber matrix by in-situ polymerization, and the MnO2 content is controlled at 30%-40%; The electrolyte is a gel electrolyte, with polyvinyl alcohol (PVA) as the skeleton, and a mixed lithium salt of lithium perchlorate (LiClO4) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) is incorporated, the molar ratio of the two is 1:2-1:3, the total concentration of the lithium salt is maintained at 3-5 mol / L, and contains 0.5%-1% of the total mass of the electrolyte, the fluorine-containing organic compound ammonium perfluorooctanoate (APFO); or an ionic liquid electrolyte, composed of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBFx) and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) salt (BMIMNTf2) The mixed ionic liquid system, the volume ratio is 2:1-3:1, and contains 0.01%-0.03% of the total mass of the vanadium-containing organic compound acetylacetonate vanadium (V(Acac)3); The device structure adopts a coaxial fiber structure, with MWCNTs-NGQDs composite fiber as the inner core, a layer of MnO2-PPy composite fiber coated on the outside, and a gel electrolyte layer wrapped on the outermost layer with a thickness of about 50-100μm; or a woven device structure, in which multiple fibrous supercapacitors are woven into a two-dimensional or three-dimensional network structure.
2. The fiber-shaped supercapacitor according to claim 1, characterized in that: The preparation method of the composite carbon nanotube fiber electrode is: using electrospinning, accurately controlling the spinning voltage at 15-25 kV, the receiving distance at 10-20 cm, the flow rate at 0.5-1 mL / h, and adding 0.5%-1% of the surfactant sodium dodecyl sulfate (SDS) to the precursor solution.
3. The fiber-shaped supercapacitor according to claim 1, characterized in that: The preparation method of the gel electrolyte comprises: mixing polyvinyl alcohol, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide and ammonium perfluorooctanoate in proportion, and performing stirring, heating and degassing treatment to uniformly disperse the components.
4. The fiber-shaped supercapacitor according to claim 1, characterized in that: The preparation method of the ionic liquid electrolyte comprises: mixing 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt according to a set volume ratio, adding vanadium-containing organic compound vanadium acetylacetonate, and stirring evenly under the protection of an inert gas.
5. The fiber-shaped supercapacitor according to claim 1, characterized in that: The assembly process of the fiber-shaped supercapacitor with the coaxial fiber structure is completed on a continuous roll-to-roll production process line, and the parameters of each link are monitored in real time throughout the process from electrode fiber preparation, electrolyte coating to device packaging.
6. The fiber-shaped supercapacitor according to claim 1, characterized in that: It also includes a performance monitoring and control system, which is an in-situ cyclic voltammetry (CV), constant current charge and discharge (GCD) and electrochemical impedance spectroscopy (EIS) joint testing system for real-time tracking of the specific capacitance, internal resistance and coulombic efficiency of the fibrous supercapacitor during the preparation process and aging stage. When the specific capacitance drops by more than 3% or the internal resistance increases by more than 5%, the subsequent process parameters are automatically adjusted.
7. The fiber-shaped supercapacitor according to claim 1, characterized in that: The device is also equipped with a microstructure detection device, which is an online monitoring system that combines a scanning electron microscope (SEM) with a transmission electron microscope (TEM). The SEM is used to capture the surface morphology and pore conditions of the material, and the TEM is used to analyze the internal structure of the grains and nanostructure characteristics. If an abnormality is found, the preparation process can be adjusted immediately.
8. The fiber-shaped supercapacitor according to claim 1, characterized in that: Applied to the energy supply of smart clothing, fiber-shaped supercapacitors are woven into clothing fabrics and work together with other energy harvesting devices to collect human motion energy and ambient light energy to continuously power the built-in components of the clothing.
9. The fiber-shaped supercapacitor according to claim 1, characterized in that: It is used for self-powering of IoT sensors and integrated into IoT sensor nodes. It uses high power density and fast charging and discharging characteristics to capture and store environmental micro-vibrations and temperature difference energy.
10. The fiber-shaped supercapacitor according to claim 1, characterized in that: When synthesizing the electrolyte, an organic additive containing ethylene glycol is added at a weight percentage of 5% to 10% of the total raw material weight to ensure that the capacitance decay amplitude is less than 15% in a low temperature environment of -20°C; The electrode material incorporates 0.5% to 1% of the material mass of organic small molecules containing disulfide bonds. When microcracks appear inside the electrode, the disulfide bonds are broken and reconnected under heat or light stimulation to repair the microcracks. Based on the micro-electromechanical system (MEMS) process, customized production of micro-fiber supercapacitors can be achieved to meet the stringent requirements of implantable medical devices, micro-sensors, etc. for tiny energy storage devices.